Training of Trainers on Enhancing Forecasting Capacities And Crop Capability Prediction Model/Tool - Amha, Yosef; Garanganga, Bradwell; Nyakutambwa, Trymore; Magagula, Futhi; Mwanza, Morton; Recha, John W.M.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The negative impact of hydro-meteorological hazards on agricultural sector oftentimes leads to food insecurity, especially in Sub-Saharan Africa (SSA). It is, therefore, incumbent upon policymakers to formulate appropriate strategies that aimed at minimizing the effects of hydro-meteorological hazards on communities and the economies. Therefore, there is a need for availability of timely and tailored climaterelated knowledge, information and products that support decision making in an effort to reduce climaterelated losses and enhance benefits. In this regard, Regional partners1 commissioned a series of studies to build a crop capacity prediction tool in order to maximize agricultural productivity while limiting the consequences of hydro-meteorological risks on the food system. This tool can assist policymakers and user communities decide on the most up-to-date crop capability based on projected climate evidence. However, for this tool to be operationalized and bring maximum impact, roving training of trainers (ToT) workshops are required for agricultural yield prediction users, seasonal climate forecast (SCF) providers, researchers, and academics. The first such ToT workshop was held in Harare, Zimbabwe, in July 2022., The third ToT workshop after Zimbabwe was held in Livingstone, Zambia, from 19 to 22 September 2023. The session was attended by around 30 professionals from the University of Zambia (UNZA), the Ministry of Agriculture, the Zambia Meteorological Department (ZMD), and other relevant departments.